2018
DOI: 10.1002/mabi.201800301
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Tyrosinase Related Protein‐2 (TRP2) Peptides to Lymph Nodes using Serum‐Derived Exosomes

Abstract: Exosomes (EXO) are considered to be versatile carriers for biomolecules; however, the delivery of therapeutic peptides using EXOs poses several challenges. In this study, the efficiency of serum‐derived EXOs in delivering tyrosinase‐related protein‐2 (TRP2) peptides to lymph nodes is determined. TRP2 peptides are successfully incorporated into EXOs, which show a uniform and narrow size distribution of around 45 nm. The TRP2‐incorporated exosomes (EXO‐TRP2) are efficiently internalized into macrophages and dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 46 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…While MPLA incorporated EXO‐PEG‐man greatly boosted releases of pro‐inflammatory cytokines, free EXO‐PEG‐man treated DCs exhibited negligible amount of TNF‐α and IL‐6 (Figure S5, Supporting Information). In our previous study, free MPLA showed reduced cytokine induction compared to EXO‐MPLA . As expected, EXO‐PEG‐man showed the highest pro‐inflammatory cytokine induction for the DC2.4 cells.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…While MPLA incorporated EXO‐PEG‐man greatly boosted releases of pro‐inflammatory cytokines, free EXO‐PEG‐man treated DCs exhibited negligible amount of TNF‐α and IL‐6 (Figure S5, Supporting Information). In our previous study, free MPLA showed reduced cytokine induction compared to EXO‐MPLA . As expected, EXO‐PEG‐man showed the highest pro‐inflammatory cytokine induction for the DC2.4 cells.…”
Section: Resultssupporting
confidence: 71%
“…To examine whether the enhanced intracellular uptake of EXO‐PEG‐man into the DC2.4 cells leads to an elevated cytokine release, the pro‐inflammatory cytokines were quantitatively measured after the treatment of EXO‐PEG‐man into the DC2.4 cells. As an immune stimulator, MPLA was incorporated into EXO‐PEG‐man . After MPLA was incorporated into EXO‐PEG‐man via co‐incubation, the MPLA embedded EXO‐PEG‐man was treated to DC2.4 cells and the released cytokines (TNF‐α and IL‐6) were measured by ELISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These advantages make them ideal biomarkers for disease diagnosis and prognosis, and a promising choice as drug delivery vehicles. For example, serum-derived exosomes have been used to deliver tyrosinaserelated protein-2 (TRP2) peptides to lymph nodes in preclinical trials (Park et al, 2018). However, the application of exosomes in clinical settings remains LncRNA-SNHG14 Breast cancer Promotes trastuzumab chemoresistance Dong et al, 2018 challenging because they are currently expensive to isolate, difficult to detect and classify due to heterogeneity, and show discrepancies between in vitro and in vivo experimental systems (Li Q et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biologically derived vesicles, e.g., cell-derived vesicles and microvesicles, have been intensively investigated as one of the alternatives for synthetic particulate systems. In particular, exosomes (EXOs) have been considered promising drug carriers because of their aqueous stability, homogeneous diameter, and biocompatibility [11][12][13]. In a previous study, serum derived EXOs had a narrow size distribution of approximately 50 nm as well as high production yield [14].…”
Section: Introductionmentioning
confidence: 99%